The xenoestrogens biphenol‐A and nonylphenol differentially regulate metalloprotease‐mediated shedding of EGFR ligands. Issue 3 (25th August 2017) - Urriola‐Muñoz, Paulina; Li, Xue; Maretzky, Thorsten; McIlwain, David R.; Mak, Tak W.; Reyes, Juan G.; Blobel, Carl P.; Moreno, Ricardo D.
Abstract : The xenoestrogens bisphenol‐A (BPA) and nonylphenol (NP) are endocrine disruptors used in the plastic polymer industry to manufacture different products for human use. Previous studies have suggested a role of these compounds in the shedding of signaling molecules, such as tumor necrosis factor α (TNF‐α). The aim of this work was to evaluate the effect of BPA and NP on the sheddase ADAM17 and its newly discovered regulators iRhom1 and iRhom2 in the release of EGFR‐ligands. We report that BPA and NP can stimulate the release of the ADAM17‐substrates HB‐EGF and TGF‐α. In cells lacking ADAM17 ( Adam17 −/− mEFs) BPA‐stimulated release of HB‐EGF, but not TGF‐α, was strongly reduced, whereas NP‐stimulated shedding of HB‐EGF and TGF‐α was completely abolished. Inactivation of both ADAM17 and the related ADAM10 ( Adam10/17 −/− mEFs) completely prevented the release of these substrates. In the absence of iRhom1, BPA‐ or NP‐stimulated release of HB‐EGF or TGF‐α was comparable to wild‐type control mEFs, conversely the BPA‐induced release of HB‐EGF was abolished in iRhom2 −/− mEFs. The defect in shedding of HB‐EGF in iRhom2 −/− mEF cells could be rescued by overexpressing iRhom2. Interestingly, the NP‐stimulated release of HB‐EGF was not affected by the absence of iRhom2, suggesting that NP could potentially activate both ADAM10 and ADAM17. We tested this hypothesis using betacellulin (BTC), an EGFR‐ligand that is a substrate for ADAM10. We found that NP, but not BPA stimulated the release of BTC in Adam17 −/−, iRhom2 −/−, or iRhom1/2 −/−, but not in Adam10/17 −/− cells. Taken together, our results suggest that BPA and NP stimulate the release of EGFR‐ligands by differentially activating ADAM17 or ADAM10. The identification of specific effects of these endocrine disruptors on ADAM10 and ADAM17 will help to provide a better understanding of their roles in cell signaling and proinflammatory processes, and provide new potential targets for treatment of reproductive or inflammatory diseases such as asthma or breast cancer that are promoted by xenoestrogens. Abstract : BPA and NP stimulate the release of EGFR‐ligands by differentially activating ADAM17 or ADAM10.